(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Congenital hypothyroidism (CH) is the most common congenital endocrine disorder and is a common, preventable cause of mental retardation and growth failure if thyroid hormone replacement is ensured at the proper time and dose. It is well documented that without L-thyroxine replacement from early life, CH causes irreversible neuro-developmental impairment. The three main causes of congenital hypothyroidism are: a) dysembryogenesis, i.e., thyroid dysgenesis, b) dyshormonogenesis and c) transient hypothyroidism. Thyroid dysgenesis includes agenesis and/or the complete absence of the thyroid gland.The diagnosis of CH through new born screening (NBS) program in Bangladesh has greatly contributed to the start of treatment within an adequate time frame since 1999 but the etiological diagnosis is usually delayed until the age of 3 years. This reported case of a 13 years old teenage girl emphasized the importance to find the etiology of her CH diagnosed on day 10 after her birth. The importance of assessing biochemical status of thyroid along with high resolution neck ultrasound (HRUS) and 99mTc-thyroid scintigraphy could change the entire scenario and ensure proper treatment of CH in a place far away from the capital city. Bangladesh J. Nuclear Med. 25(2): 138-142, 2022